THE IMPACT OF BRAND PERSONALITY AND SELF-IMAGE CONGRUENCEON STUDENT’S BRAND ATTACHMENT OF APPLE PRODUCTS - Manoppo, Chiesa Octavianus; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2020)
Abstract: Creating an attachment between brand and consumer represents a key of success for a company for many years to come. Consumers intend to buy a product that describes their self-image in a way that they want to be seen by others. The purpose of this study is to understand the impact of brand personality and self-image congruence on studentâ€™s brand attachment of Apple products, as for now Apple products are known to have great quality of products on their field which differentiate the product with other type of products. The population of this research is the student of Sam Ratulangi University and the quantitative method is used in this research. In order to collect the data, questionnaires were distributed to 100 Sam Ratulangi University students. The result of this research shows that brand personality has positive relationship toward brand attachment with significant influence, and self-image congruence also has positive relationship toward brand attachment with significant influence. It is recommended for the marketers to utilize on both variables in order to increase the tendencies of people in buying the product.Â Keywords: brand personality, self-image congruence, brand attachment